2013
DOI: 10.1007/s13205-013-0139-z
|View full text |Cite
|
Sign up to set email alerts
|

Statistical optimization of process parameters for the production of tannase by Aspergillus flavus under submerged fermentation

Abstract: Production of tannase by Aspergillus flavus (MTCC 3783) using tamarind seed powder as substrate was studied in submerged fermentation. Plackett–Burman design was applied for the screening of 12 medium nutrients. From the results, the significant nutrients were identified as tannic acid, magnesium sulfate, ferrous sulfate and ammonium sulfate. Further the optimization of process parameters was carried out using response surface methodology (RSM). RSM has been applied for designing of experiments to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…After the optimum period of fermentation, tannase activity declined possibly due to exhaustion of nutrients in the medium. The present results are in close accordance to Mohan et al ( 2014a , b ) who studied the applications of RSM for the production of tannase by Aspergillus foetidus (MTCC 3557) using redgram husk as substrate under submerged fermentation. The reported optimum conditions were tannin content of 3.1 %, fermentation period of 97 h, temperature of 35.5 °C and pH of 5.5.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After the optimum period of fermentation, tannase activity declined possibly due to exhaustion of nutrients in the medium. The present results are in close accordance to Mohan et al ( 2014a , b ) who studied the applications of RSM for the production of tannase by Aspergillus foetidus (MTCC 3557) using redgram husk as substrate under submerged fermentation. The reported optimum conditions were tannin content of 3.1 %, fermentation period of 97 h, temperature of 35.5 °C and pH of 5.5.…”
Section: Discussionsupporting
confidence: 92%
“…The reported optimum conditions were tannin content of 3.1 %, fermentation period of 97 h, temperature of 35.5 °C and pH of 5.5. Similar kind of results have been reported in case of tannase production from Aspergillus awamori MTCC 9299 and Aspergillus flavus (Beniwal and Chhokar 2010 ; Mohan et al 2014a , b ). Bhoite et al ( 2015 ) also studied production of tannase by P. verrucosum using coffee pulp as substrate and obtained maximum tannase production at 96 h of fermentation period.…”
Section: Discussionsupporting
confidence: 82%
“…The obtained precision values of 11.224 and 10.433 for crystallinity index and nanocellulose yield models, respectively. The obtained adequate precision values for both models were well above 4, which indicates an adequate signal, and further suggests that the proposed models can be used to navigate the design space Karim et al 2014;Mohan et al 2014).…”
Section: Model Selection and Statistical Analysismentioning
confidence: 61%
“…Mohan et al ( 2014 ) also observed that with increase of metal dose Cr removal increases in A. flavus . Masood and Malik ( 2011 ) also find out that chromium adsorption was increased by Bacillus sp.…”
Section: Discussionmentioning
confidence: 85%